2002
DOI: 10.1002/hbm.10071
|View full text |Cite
|
Sign up to set email alerts
|

Novelty detection and repetition suppression in a passive picture viewing task: A possible approach for the evaluation of neuropsychiatric disorders

Abstract: The applicability of functional magnetic resonance imaging (fMRI) in patients with Alzheimer's disease (AD) or schizophrenia is frequently limited by cognitive impairment, which prevents the adequate execution of complex tasks. An experimental design that puts only minor demands on the patients' cognitive ability but engages disease-relevant brain structures would be of benefit. Novelty detection and repetition suppression are two basic components of memory that might be used to investigate specific brain area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Both rodent and human HPC lesions result in deficits in novelty-related behaviors (Ranganath and Rainer 2003) and human neuroimaging demonstrates engagement of these regions during novelty processing (Stern et al 1996;Gabrieli et al 1997;Jessen et al 2002;Kohler et al 2005;Bunzeck and Duzel 2006;Yassa and Stark 2008;Blackford et al 2010;Howard et al 2011). In our study, we found that novelty-related engagement of the HPC and surrounding cortical MTL was dynamic: MTL novelty responses were greater at the beginning of the experiment and slowly declined as individuals gained experience with novelty.…”
Section: Novelty Processing In the Mtlmentioning
confidence: 47%
See 1 more Smart Citation
“…Both rodent and human HPC lesions result in deficits in novelty-related behaviors (Ranganath and Rainer 2003) and human neuroimaging demonstrates engagement of these regions during novelty processing (Stern et al 1996;Gabrieli et al 1997;Jessen et al 2002;Kohler et al 2005;Bunzeck and Duzel 2006;Yassa and Stark 2008;Blackford et al 2010;Howard et al 2011). In our study, we found that novelty-related engagement of the HPC and surrounding cortical MTL was dynamic: MTL novelty responses were greater at the beginning of the experiment and slowly declined as individuals gained experience with novelty.…”
Section: Novelty Processing In the Mtlmentioning
confidence: 47%
“…Evidence from humans, nonhuman primates, and rodents points to a specialized brain system for the detection of novelty, centered around the hippocampus (HPC) and medial temporal lobe (MTL) memory system (Ranganath and Rainer 2003). It is now well documented that the HPC and MTL respond robustly to novel stimuli (Gabrieli et al 1997;Jessen et al 2002;Kohler et al 2005;Bunzeck and Duzel 2006;Yassa and Stark 2008;Blackford et al 2010;Howard et al 2011). However, relatively little is known about how these responses are modulated by prior experience.…”
mentioning
confidence: 99%
“…Human functional neuroimaging studies have also implicated MTL structures, including the hippocampus, entorhinal cortex and the amygdala, in some aspects of novelty detection (Daselaar et al, 2004;c.f. Eichenbaum, 1999;Fischer et al, 2002;Fried et al, 1997;Grunwald et al, 1998;Henke et al, 1999;Hunkin et al, 2002;Jessen et al, 2002;Martin, 1999;Opitz et al, 1999;Strange and Dolan, 2001;Wright et al, 2003;Yamaguchi et al, 2004). In addition, a recent computational model of infant habituation (Sirois and Mareschal, 2004) includes the hippocampus and entorhinal cortex as critical functional units.…”
Section: Discussionmentioning
confidence: 98%
“…In cognitive tasks the involvement of these regions is usually associated with perceiving and manipulating visuospatial information and the deactivation of these regions is associated with perceptual priming [Cabeza and Nyberg, 2000]. A decrease in activity in occipito-temporal regions, including the fusiform gyrus, is a common finding amongst studies on perceptual priming of objects and visual scenes [e.g., Jessen et al, 2002] and it has even been observed for objects presented from different viewpoints or different exemplars of a same object [e.g., Vuilleumier et al, 2002]. Interestingly, those regions showed a decrease in activity in the encoding stage when the brain activity elicited by the presentation of the second related segment was compared with the brain activity elicited by the first segment , thus suggesting that a segment of a picture could prime the processing of another one.…”
Section: Brain Activity For the Low Discriminability Condition Relatimentioning
confidence: 99%